IMI Python: Upgraded CS Circles web‐based Python course. Issue 3 (16th March 2016) - Djokic‐Petrovic, Marija; Pritchard, David; Ivanovic, Milos; Cvjetkovic, Vladimir
ABSTRACT: The rapid growth of student demand for flexible education and learning alternatives has caused a significant increase in web‐based programming course offerings. In order to ensure easy and enjoyable ways of acquiring knowledge, many web‐based solutions have customized the design and content to student needs. This paper introduces a project of the Institute for Mathematics and Informatics (IMI) called IMI Python, an interactive online course. It is based on the open‐source Computer Science Circles (CS Circles) project. IMI Python aims to assist the target audience, primarily students, learn a spectrum of Python knowledge. The benefits of this enhanced system are multiple, both for students and their teachers. The course content is structured and divided by levels: basic, medium, and advanced. Flexible navigation through the different levels of difficulty and lesson units allows students to easily review any forgotten material and adopt new knowledge. Teachers have the ability to follow the progress of individual students or all students in a level, and communicate with them about their work. Teachers and students can communicate within the system to discuss individual exercises through a simple user interface. The system is enhanced with the possibility of testing students' knowledge through quizzes. Quizzes are visible at assigned time intervals and are worth a certain number of points. By tracking students' results, teachers can determine whether the site has enough quality material and what can contribute to its improvement. © 2016 Wiley Periodicals, Inc. Comput Appl Eng Educ 24:464–480, 2016; View this article online atwileyonlinelibrary.com/journal/cae ; DOI10.1002/cae.21724